The Role of Environmental Law in Addressing Climate Change: An Analysis of Law Enforcement and Compliance in Indonesia - Kesek, Meike Negawati (International Journal of Business, Law, and Education, 2025)
Climate change poses a significant threat to environmental sustainability, public health, and economic development, particularly in vulnerable countries like Indonesia. As a nation rich in natural resources and biodiversity, Indonesia plays a crucial role in global climate mitigation efforts. This study examines the role of environmental law in addressing climate change in Indonesia, with a specific focus on the enforcement and compliance mechanisms within the national legal framework. Using a qualitative socio-legal approach, the study analyzes legislative documents, policy reports, and court decisions, complemented by interviews with government officials, legal experts, and civil society organizations. The findings reveal that while Indonesia has enacted a comprehensive set of environmental laws aligned with international commitments such as the Paris Agreement, the implementation remains weak due to institutional fragmentation, limited enforcement capacity, and low compliance among corporate and community actors. Civil society plays a vital role in bridging enforcement gaps, although challenges persist in ensuring judicial independence and equitable access to justice. The study concludes that enhancing legal enforcement, institutional coordination, and public participation is essential for strengthening Indonesia’s environmental governance and achieving its climate objectives.